The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1055/s-0038-1653825
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Characterization of High Purity Factor IX Concentrates for the Treatment of Hemophilia B

Abstract: SummaryThis study employed sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis and immunoblotting to assess the purity of seven high purity factor IX concentrates: Aimafix (Aima), AlphaNine-SD (Alpha Therapeutic), Factor IX VHP (Biotransfusion), Immunine (Immuno), Mononine (Armour Pharmaceutical), Nanotiv (Kabi Pharmacia), and 9MC (Blood Products Laboratory). The mean specific activity of these products ranged from 68 U factor IX/mg (Aimafix) to 246 U factor IX/mg (Mononine). SDS-PAGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…A recently proposed application of the new sTF-based assay for plasma FVIIa levels is to screen commercial clotting factor concen trates for contamination by potentially thrombogenic materials [30], Another poten tial application is to monitor plasma FVIIa levels during recombinant FVIIa therapy for bleeding disorders such as hemophilia [8,31] , 32-43]. In particular, the Northwick Park Heart Study found a significant correlation between ele vated plasma FVII:C levels and risk of isch emic heart disease [6], Interestingly, long term follow-up of Northwick Park Heart Study participants revealed a strong correla tion between FVII:C and fatal (but not nonfatal) events of ischemic heart disease [42], In another large prospective study, the Prospec tive Cardiovascular Münster study (PRO CAM), a correlation between plasma FV1I:C and coronary events was also reported, but with less significance than the Northwick Park Heart Study [32], Long-term follow-up of PROCAM study participants showed no statistically significant difference in FVILC levels among men who had or had not experi enced coronary events [36].…”
Section: Measurem Ent Of Plasm a Levels Of Fviiamentioning
confidence: 99%
“…A recently proposed application of the new sTF-based assay for plasma FVIIa levels is to screen commercial clotting factor concen trates for contamination by potentially thrombogenic materials [30], Another poten tial application is to monitor plasma FVIIa levels during recombinant FVIIa therapy for bleeding disorders such as hemophilia [8,31] , 32-43]. In particular, the Northwick Park Heart Study found a significant correlation between ele vated plasma FVII:C levels and risk of isch emic heart disease [6], Interestingly, long term follow-up of Northwick Park Heart Study participants revealed a strong correla tion between FVII:C and fatal (but not nonfatal) events of ischemic heart disease [42], In another large prospective study, the Prospec tive Cardiovascular Münster study (PRO CAM), a correlation between plasma FV1I:C and coronary events was also reported, but with less significance than the Northwick Park Heart Study [32], Long-term follow-up of PROCAM study participants showed no statistically significant difference in FVILC levels among men who had or had not experi enced coronary events [36].…”
Section: Measurem Ent Of Plasm a Levels Of Fviiamentioning
confidence: 99%
“…Activated FIX (FIXa) is present in rFIX and pdFIX preparations at low levels as evidenced by immunological and enzymatic analysis (55,56). Analysis of rFIX production batches using a nonactivated partial thromboplastin time assay (as described in the European Pharmacopoeia) shows that FIXa levels are consistently below the European Pharmacopoeia test limits.…”
Section: Puritymentioning
confidence: 99%
“…Our most recent study [8] extended the analysis by eval uating seven high-purity concentrates tested with a series of sensitive assays for potentially thrombogenic materials, including sodium dodecyl sulfate-polyacrylamide gel elec trophoresis (SD S-P A G E ) under both reducing and nonre- ducing conditions, immunoblotting to detect factor V II, IX , X and prothrombin, chromogenic assay to detect acti vated clotting factors and the highly sensitive clot-based assay o f Morrissey et al [24] to detect factor V ila activity. In addition to AlphaNine-SD and Mononine, the fol lowing high-purity factor IX products were analyzed: Aimafix (Aima) Factor IX V H P (BioTransfusion), Immunine (Immuno), Nanotiv (Kabi Pharmacia) and 9 M C , now known as Replinine (Blood Products Laboratory).…”
Section: Relative Purity Of Factor IX Concentratesmentioning
confidence: 99%
“…Evaluation o f these products in in vitro assays [5][6][7][8] and after infusion into animals [9][10][11][12] has suggested that they will be less thrombogenic in vivo. Following infusions in patients with hemophilia B, they have exhibited reduced activation o f the coagulation cas cade [7,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation